An experimental investigation on thermal efficiency of a compression ignition engine fueled with five gasoline-like fuels. (1st November 2017) - Yu, Linjun; Shuai, Shijin; Li, Yanfei; Li, Bowen; Liu, Haoye; He, Xin; Wang, Zhi
Highlights: Five gasoline-like fuels were tested with PPCI and MPCI modes. Gasoline/PODE fuel achieved highest thermal efficiency of about 48.8% for both modes. NOx and soot emissions were lower than the limit of Euro VI standard in PPCI mode. Abstract: Partially Premixed Compression Ignition (PPCI) and Multiple Premixed Compression Ignition (MPCI) are two high efficiency and clean combustion strategies. This paper presents an experimental investigation on the efficiency of PPCI and MPCI combustion using five gasoline-like fuels: gasoline, gasoline/ethylhexyl-nitrate (EHN) blends, gasoline/diesel blends, gasoline/polyoxymethylene dimethyl ethers (PODEn) blends, gasoline/diesel/PODEn blends, denoted as G, GE, GD, GP, GDP, respectively. The study was conducted using a single cylinder engine that was retrofitted from a production Euro IV diesel engine. The results showed that in PPCI mode, the order of thermal efficiency from the highest to the lowest was GP, G, GDP, GE, and GD, while the order in MPCI mode was GP, GDP, GE, G, and GD. The thermal efficiency of MPCI mode was higher than that of PPCI mode, except for GP, whose thermal efficiency was the highest of about 48.8% for both modes due to the early CA50 and short combustion duration. In PPCI mode, NOx and soot emissions were below 0.4 g/kWh and 0.01 g/kWh, respectively, satisfying the Euro VI emission standard. NOx emission in MPCI mode can meet the requirement of Euro VI. However, the soot emission exceeded the limit because the second stage combustion was partially diffusion combustion, implying an extra Gasoline Particle Filter (GPF) was needed to meet the Euro VI standard. This study indicates that PPCI injection strategy alone and MPCI injection strategy with GPF are two potential ways of retrofitting a Euro IV engine to meet the Euro VI emission standard. GPF increases manufacturing cost, but higher thermal efficiency in MPCI mode could reduce the total cost of ownership due to the lower fuel consumption.